2021
DOI: 10.3389/fpsyt.2021.719125
|View full text |Cite
|
Sign up to set email alerts
|

Natural Language Processing as an Emerging Tool to Detect Late-Life Depression

Abstract: Late-life depression (LLD) is a major public health concern. Despite the availability of effective treatments for depression, barriers to screening and diagnosis still exist. The use of current standardized depression assessments can lead to underdiagnosis or misdiagnosis due to subjective symptom reporting and the distinct cognitive, psychomotor, and somatic features of LLD. To overcome these limitations, there has been a growing interest in the development of objective measures of depression using artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…Moreover, it is possible for the LLM to integrate with telehealth services especially for those who have a disability [53]. In addition, it is believed that LLMs are even able to detect later-life depression, which is a kind of major public health concern that occurs in the older generation, as the name states [65]. NLP analyzes the way people talk and also the speed and pitch they use in order to understand their speech patterns [65].…”
Section: Symptom Diagnosismentioning
confidence: 99%
“…Moreover, it is possible for the LLM to integrate with telehealth services especially for those who have a disability [53]. In addition, it is believed that LLMs are even able to detect later-life depression, which is a kind of major public health concern that occurs in the older generation, as the name states [65]. NLP analyzes the way people talk and also the speed and pitch they use in order to understand their speech patterns [65].…”
Section: Symptom Diagnosismentioning
confidence: 99%
“…Recent studies in patients with mood disorders have demonstrated that a number of acoustic measures characterized by source features from the vocal folds (e.g., jitter, shimmer, harmonics-to-noise ratio (HNR), lter features from the vocal tract (e.g., F1 and F2 formants), spectral features (e.g., Mel Frequency Cepstral Coe cients (MFCCs), and prosodic/melodic features (e.g., fundamental frequency (F0)), speech intensity, speed, and pause duration) have been shown to be altered in individuals with depression (33).…”
Section: Audio and Sentiment Analysismentioning
confidence: 99%
“…The majority of clinically relevant studies are unfortunately based on smaller and less representative data samples. These are usually directly used for analysis and become unsuitable for training a new generation of models (33).…”
Section: Audio Streammentioning
confidence: 99%
“…In psychiatry, NLP can be used for IE from unstructured EHR and speech analysis on patient speech data [63,64]. NLP can help in the screening, early diagnosis, or severity estimation of various diseases such as depression [63], bipolar disorder [65], dementia [66][67][68], psychosis [69,70], and schizophrenia [71]. Dai…”
Section: Psychiatrymentioning
confidence: 99%